Preferensi Masyarakat terhadap Pola Pemanfaatan Lahan Hutan Rakyat di Desa Lekopancing, Kecamatan Tanralili, Kabupaten Maros. - Arman Syahrul Amin; Emban Ibnurusyd Mas'ud; Mas'ud Junus (Jurnal Hutan dan Masyarakat, 2017)
This study describes the community preferences on land use arrangement in Lekopancing Village, Tanralili Subdistrict, Maros District. The results showed that the preferences of society towards the selection patterns of land use private forest determined by social factors, economic factors, and external factors. Social factors such as success stories of two persons in this village whom earn a large income from the plantation of Gmelina arborea (white teak), which is accompanied by social capital in the form of local knowledge and cultural system based on reciprocity. Economic factors, that is people felt motivated caused by increased income through the white teak plantation. External factors, such as KBR incentive programs and the provision of forestry extension worker, become the driving factors too.